Evaluating the impacts of using the Pod Borer Resistant Cowpea variety in Nigeria: Research design and characteristics of study participants - Andam, Kwaw S.; Amare, Mulubrhan; Zambrano, Patricia; Chambers, Judith A.; Bamiwuye, Temilolu; Fasoranti, Adetunji; Nwagboso, Chibuzo; Mockshell, Jonathan (International Food Policy Research Institute, 2023)
Dr. Kwaw Andam delivered these slides during the African Conference of Agricultural Economists in Durban, South Africa, in September 2023. The study was funded by the USAID and CGIAR Initiative on National Policies and Strategies